El derecho canónico en «Estudios Eclesiásticos»: Balance de un siglo II (1999-2021) - Campo Ibáñez, Miguel ca. 21. Jh. (Estudios eclesiásticos, 2022)
In 1999, with the end of the twentieth century, the journal Estudios Eclesiasticos, in its annual monograph on canon law, published a chronicle of the presence of canonists from 1922, the year of the journal’s birth, until that year. The purpose of the present study is to take up that chronicle and present in detail, up to 2021, the canonical publications in the annual monographs that the journal dedicates to canon law (last issue of each year). The balance of the presence of canon law in Estudios Eclesiasticos is clearly positive. The chronicle of the presence of canon law in Estudios Eclesiasticos is an excellent testimony of the work of Spanish canonists throughout these 100 years, with special attention to the years 1999-2021, and a good research resource available to the cultivators of canon law and ecclesiastical law.